Therapeutic effects and mechanisms of Tripterygium wilfordii extracts in rheumatoid arthritis: a systematic review and meta-analysis of preclinical studies - Kai Chen; Xiaoying Chen; Shuai Huang; Lingling Zhou; Xueping Zhou; Yan Lu; Zhe Feng (Scientific Reports)
Abstract Tripterygium polyglycosides (TG), Triptolide (TP), and Celastrol (CEL), which are extracts from Tripterygium wilfordii Hook F (TwHF), are renowned for their anti-inflammatory and immunomodulatory properties in the treatment of rheumatoid arthritis (RA). However, a comprehensive systematic review and meta-analysis of preclinical evidence supporting the use of Tripterygium wilfordii extracts for RA has not yet been conducted. This study aimed to conduct a systematic review and meta-analysis to evaluate the therapeutic effects and potential underlying mechanisms of Tripterygium wilfordii extracts in CIA model of RA. Six electronic databases, including PubMed, Embase, Web of Science, Cochrane Library, Scopus, and Ovid, were searched from their inception to June 2024. The methodological quality was assessed via SYRCLE’s risk of bias tool. Statistical analyses were performed using Stata 18.0 software and Review Manager 5.4.1 software. This study included 32 articles involving 568 animals. The results revealed that Tripterygium wilfordii extracts significantly reduced joint manifestations (arthritis index, paw swelling degree, and paw thickness); histopathological changes in joints (histopathological score, cartilage damage, bone destruction, synovial hyperplasia, pannus formation, and inflammatory cell infiltration); levels of related cytokines (TNF-α, IL-1β, IL-6, IL-23, IFN-γ, and IL-17); anti-type II collagen antibodies; and T-cell subsets (CD4+ T cells, Th1 cells, and Th17 cells). Moreover, Tripterygium wilfordii extracts significantly increased the levels of relevant cytokines (IL-10, IL-4, and TGF-β) and the number of Treg cells compared with those in the control group. However, animal species and sex, extract category and dosage, and treatment duration were identified as important factors influencing the above results. Tripterygium wilfordii extracts (TG, TP and CEL) exhibit promising therapeutic effects and mechanisms in the treatment of RA. But the effect characteristics and mechanisms vary among different Tripterygium wilfordii extracts. These specific effects and mechanisms also vary depending on the treatment duration and dosage.